Hyperbaric oxygen therapy for the treatment of Steinberg I and II avascular necrosis of the femoral head: a report of fifteen cases and literature review - Motasem Salameh (14146794) (2022)
Purpose This article aimed to report a case series of pre-collapse avascular necrosis of the femoral head treated with hyperbaric oxygen and review the most recent literature on the topic. Methods The data from a prospectively followed registry of 15 patients with Steinberg I and II avascular necrosis of the femoral head was collected. Functional outcome, pain scores, and radiographic changes at an average follow-up of 22 months were analyzed and reported. Results Thirteen patients had satisfactory outcome at final follow-up with an average Oxford hip score of 37.3, pain scores were significantly improved at final follow-up (P < 0.001), and 26.7% of hips progressed to collapse on follow-up radiographs with no complications reported in all patients. Conclusion Hyperbaric oxygen treatment for pre-collapse avascular necrosis of the femoral head is considered a safe alternative with satisfactory clinical and radiological outcomes and low complications rate. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00264-021-05120-3